Hepatic involvement in major respiratory viral infections - Rzymski, Piotr; Dobrowolska, Krystyna; Brzdęk, Michał; Zarębska-Michaluk, Dorota; Flisiak, Robert (Clinical and Experimental Hepatology, 2025)
Common respiratory viral pathogens, including SARS-CoV-2, influenza viruses, and respiratory syncytial virus (RSV), can lead to extrapulmonary manifestations, including clinically significant liver involvement. This review synthesizes current evidence on the epidemiology, mechanisms, and prognostic implications of hepatic injury associated with these viruses. We discuss the distinct mechanisms of liver dysfunction, ranging from the possibility of direct viral infection of hepatocytes to indirect effects of systemic inflammatory responses, hypoxic injury, preexisting liver disease, and drug-related hepatotoxicity. Liver involvement in COVID-19 has been explored to a much greater extent than in the case of influenza or RSV infections, highlighting the need for further studies. Clinically, recognizing liver involvement in respiratory viral infections is crucial, particularly in high-risk populations such as patients with chronic liver disease, transplant recipients, and children. We underscore the importance of integrating hepatic evaluation into the clinical approach to severe respiratory viral illnesses to improve patient outcomes.